A case of infective endocarditis associated with atopic dermatitis perioperatively treated with dupilumab. (3rd October 2019) - Nakanishi, Mika; Oota, Eri; Tomita, Yukihiko; Kato, Takeshi; Imanishi, Toshihiro
Abstract: Background: Several case reports and reviews support a relationship between atopic dermatitis (AD) and infective endocarditis (IE). Here, we present a case of severe AD suspected of causing IE. Case presentation: A 21-year-old man with severe AD was admitted to our hospital due to unidentified fever, syncope, and headache. He was diagnosed with IE with cerebral embolism and mitral regurgitation. Before elective cardiac surgery, he was subcutaneously administered dupilumab for 2 months to control AD. Dupilumab improved AD, and cardiac surgery was performed without complications. Conclusions: Dupilumab may be effective in AD cases as preparation for cardiac surgery.